Markov Chain Analysis to Predict Instant Noodle Brand Switching (Case Study: Indomie and Mi Gaga) - Fitriani; Besse Arnawisuda Ningsi; Irvana Arofah (Ekspektra : Jurnal Bisnis dan Manajemen, 2024)
Competition in the use of instant noodle brands in Indonesia makes the instant noodle industry need to conduct market share analysis. One of the market share analyses that can be used is the Markov chain analysis. Markov chain is a mathematical model that describes a system that undergoes a change in status from one state to another stochastically with the aim of seeing the transition of the community in changing the choice of Instant Noodle brands. The Instant Noodle brands used as objects are Indomie, Mi Gaga, and other brands. In this study, the data used is primary data, which is obtained by distributing questionnaires to the people of Pagedangan District as many as 100 respondents were selected using the purposive sampling method. This study aims to determine the prediction results of instant noodle brand switching opportunities and determine the state of market share (market share) of instant noodle brands using Markov Chain. The results of this study indicate the displacement of consumers from the three instant noodle products, namely Indomie, Mi Gaga, and Other Brands, where the probability of Indomie consumer displacement in the next 6 periods will be predicted to increase from 0 by 0.54 or 54%, in Mi Gaga by 0.41 or 41%, while in other brands only 0.05 or 5%. Furthermore, in the Market share of the three instant noodle products, namely Indomie, Mi Gaga, and Other Brands in the next 6 periods, the largest percentage is Indomie, which is 52.62%, while Mi Gaga is 43.11%, and other brands are only 4.28%. This shows that the Indomie sequence is the most in-demand by respondents.